Governance of the Entrepreneurial Threshold Firm: A Knowledge‐based Perspective - Zahra, Shaker A.; Filatotchev, Igor (Journal of Management Studies, 2004)
ABSTRACTBy building on a knowledge‐based view of the firm, this paper addresses a relatively unexplored area of roles and dynamics of corporate governance in younger, threshold firms that are undergoing a transition from the emergence to the professional management stage. Our analysis is focused on the process of capability development, exploring the effect of the asymmetry in knowledge that often exists between directors and senior managers on the governance of threshold firms. We examine the key sources of this asymmetry, explore ways directors and senior executives learn, and then discuss the implications of this learning on the evolution of governance systems in the threshold firm.